PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI PAKAIAN DI H&M SUMMARECON MALL BEKASI - Azizah Nur Syamsiyah; Widi Winarso (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
This research aims to determine simultaneously and partially the independent variables, namely brand image, consumer reviews and product quality, the dependent variable is buying interest. The method used in this research is a quantitative method. The population in this study were all consumers of jiniso.id jeans according to the criteria, namely women, aged 15-17 years, and domiciled in Bekasi. The sampling technique was purposive sampling with the hair formula and the Multiple Linear Regression Data Analysis method Based on the results of the study, the Brand Image variable has a partial positive effect on Purchase Intention which states that brand image has an effect on interest buy. Consumer Reviews variable has a negative influence on Purchase Intention which states that consumer reviews have no effect on purchase intention and Product Quality Variable has a positive influence partially to Purchase Interest which states that product quality affects purchase intention. Brand Image, Consumer Reviews and Product Quality simultaneously have a positive effect on the Purchase Intention Variable with a value. Then the determination test (R2) resulted in a correlation between the three variables Brand Image (X1), Consumer Reviews (X2) and Product Quality (X3) on Purchase Intention (Y) of 48.7%.